Low-dose tertiary prophylactic therapy reduces total number of bleeds and improves the ability to perform activities of daily living in adults with severe haemophilia A: a single-centre experience from Beijing. Issue 2 (March 2016) - Hua, Baolai; Lian, Xiaoyun; Li, Kuixing; Lee, Adrienne; Poon, Man-Chiu; Zhao, Yongqiang
Abstract : Full-dose prophylaxis treatment for persons with haemophilia is not affordable in China due to its economic constraints, particularly in adults requiring higher clotting factor (CFC) doses. Low-dose tertiary prophylaxis for adults with severe haemophilia A (SHA) in Beijing became feasible and implemented when government insurance covering 85% CFC cost in Beijing began in December 2009. The aim of this study was to evaluate the benefits of low-dose tertiary prophylaxis in SHA adults. Analysis of data on 33 patients on low-dose tertiary prophylaxis (5–10 IU/kg, two to three times per week) at the Haemophilia Treatment Center, Peking Union Medical College Hospital between December 2009 and December 2013. The 33 patients (age 18–60 years, mean 33.4) were on prophylaxis for 20.8 ± 9.9 months (compared with prior on-demand therapy for 20.0 ± 11.7 months). Prophylaxis resulted in significant decrease in annual bleeding rate (ABR, 11.8 ± 7.6 vs. 41.5 ± 20.7, 71.1% reduction, P  < 0.0001), and significant improvement in Functional Independence Score in Haemophilia (FISH) measurement reflecting improvement in self-care and mobility. Radiologic (Pettersson) joint score was neither improved nor deteriorated. Ten of the 33 patients originally wheel chair and bed-bound began to walk and function independently in their daily lives. Low-dose tertiary prophylaxis for adults with SHA in China is feasible and beneficial. Although the average ABR remained high, a significant improvement in self-care and mobility measured by FISH was observed. These promising clinical experiences form the basis for further formal studies with more defined therapeutic protocol and outcome measures for affordable prophylaxis regimens in haemophilia adults in China.